Optimal control of a batch crystallization process - Rehbock, Volker; Livk, Iztok (American Institute of Mathematical Sciences, 2007)
A dynamic model of an aluminium trihydroxide batch crystallization is considered in this work. The process model, which takes into account kinetics of nucleation, growth and agglomeration, is based on the mass balance of the process and the population balance of the dispersed crystals. Assuming that the temperature of the solution and the seeding policy are variable, optimal control techniques are applied to the model to optimize various performance criteria. Some interesting numerical results for the behaviour of the model are presented.